2017
DOI: 10.21833/ijaas.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Financial development, trade openness and economic growth in Pakistan: A granger causality approach

Abstract: This study aims to examine the direction of causality between financial development, trade openness and economic growth in Pakistan over the period 1970 to 2014. For this undertaking, statistical tools such as ADF and P-P unit root tests have been used to check stationery of the series and Cointegration test has been used to determine the long run relationship between the study variables. The causality relationship among variable is examined by Granger causality approach. The result of ADF test revealed that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…That given all the efforts of Saudi governments to diversify the economic activities through its attempts, improving the distribution of economic activities across urban areas, the map of the distribution of production units between all Kingdom areas has not changed much. Chandio et al (2017) confirmed that trade openness and diversification play an important role in boosting economic growth in Pakistan. Indeed, economic development is an important factor of regional planning and it is one of the strongest factors for regional cooperation.…”
Section: Literature Reviewmentioning
confidence: 72%
“…That given all the efforts of Saudi governments to diversify the economic activities through its attempts, improving the distribution of economic activities across urban areas, the map of the distribution of production units between all Kingdom areas has not changed much. Chandio et al (2017) confirmed that trade openness and diversification play an important role in boosting economic growth in Pakistan. Indeed, economic development is an important factor of regional planning and it is one of the strongest factors for regional cooperation.…”
Section: Literature Reviewmentioning
confidence: 72%
“…In some of those studies, researchers aimed to explore the effect of credit market development on economic growth by utilizing the private sector domestic credit and broad money as main indicators of credit market development (Raz, 2013; Timsina, 2014; Sassi & Sami, 2014; Mishra, Das, & Pradhan, 2009). Some researchers included other economic indicators in the model specification such as trade openness, foreign direct investment and urbanization as control variables in addition to credit market development indicators (Altaee & Al‐Jafari, 2015; Altaee, Saied, Esmaeel, & Adam, 2014; Mohammad, Muhammad, & Abdul, 2015; Abbas, Abdul, Yuansheng, & Mumtaz, 2017; Gao & Shao, 2016). Nyasha, Kwaramba, and Coulibaly (2016) employed measures of institutions alongside, while Alpha et al (2016) included both Quasi‐Liquid Liability and interest rate spread as indicators for credit market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study used the Johansson cointegration approach. The results showed a positive effect of TO on economic growth Chandio et al (2017). premeditated influence of financial development and trade openness on Pakistan's growth of economy.…”
mentioning
confidence: 90%